1998
DOI: 10.1073/pnas.95.20.11792
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of a mammalian wound-healing trait

Abstract: Wound healing of mammalian tissue is an essential process in the maintenance of body integrity. The general mechanism of wound healing usually studied in adult mammals is repair, in contrast to the regeneration seen in more primitive vertebrates. We recently have discovered that MRL͞MpJ mice, unlike all other strains of mice tested, undergo rapid and complete wound closure that resembles regeneration. Specifically, through-and-through surgical ear hole wounds close without scarring in <4 weeks with normal gros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(147 citation statements)
references
References 29 publications
5
135
0
6
Order By: Relevance
“…This striking phenotype was first observed in the MRL mouse's ability to completely close through-and-through ear holes without scarring, to form a blastema, and to replace lost cartilage (19,20), a phenomenon similar to that seen during amphibian limb regeneration (2,3). In the present study, after right ventricular cryoinjury, the C57BL͞6 mouse healed with massive scarring and little if any new cardiomyocytes.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This striking phenotype was first observed in the MRL mouse's ability to completely close through-and-through ear holes without scarring, to form a blastema, and to replace lost cartilage (19,20), a phenomenon similar to that seen during amphibian limb regeneration (2,3). In the present study, after right ventricular cryoinjury, the C57BL͞6 mouse healed with massive scarring and little if any new cardiomyocytes.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, we have mapped the genes involved, identified a minimum of six different loci on five chromosomes, and shown that this is a complex multigenic trait (19,20).…”
mentioning
confidence: 99%
“…To identify genes associated with multigenic ear hole closure, linkage mapping studies have been conducted in a number of different MRL F2 intercrosses, including MRL Â C57BL/6 (B6) (McBrearty et al, 1998;Blankenhorn et al, 2003), MRL Â CAST/EiJ Yu et al, 2005) and MRL Â SJL/J (Masinde et al, 2001). MRL mice were originally bred from a series of crosses of four mouse strains (Murphy and Roths, 1978), AKR/J, C3H/HeDi, C57BL/6J, 65 and two final backcrosses with LG/J (LG).…”
Section: Introductionmentioning
confidence: 99%
“…FasL expression on the cell surface can be regulated by cleavage of membrane-bound FasL into soluble FasL (sFasL) by MMP-7 and MMP-3 . Unlike C3H/HeJ mice, MRL +/+ mice apparently have a propensity to produce certain metalloproteinases (Gourevitch et al, 2003), which has been linked to their unusual capacity for wound healing (McBrearty et al 1998). It is possible that their propensity to produce metalloproteinases may also play a role in the autoimmune-proneness of MRL +/+ mice.…”
Section: Discussionmentioning
confidence: 99%